Management of pregnant patients with pulmonary arterial hypertension - Zhang, Xiao; Huangfu, Zhao (Frontiers in Cardiovascular Medicine, 2022)
Pregnant individuals with pulmonary arterial hypertension (PAH) have significantly high risks of maternal and perinatal mortality. Profound changes in plasma volume, cardiac output and systemic vascular resistance can all increase the strain being placed on the right ventricle, leading to heart failure and cardiovascular collapse. Given the complex network of opposing physiological changes, strict contraception and reduction of hemodynamic fluctuations during pregnancy are important methods of minimizing the risk of maternal mortality and improving the outcomes following pregnancy. In this review, we discuss the recent research progress into pre-conception management and the various therapeutic strategies for pregnant individuals with PAH.